Re-Evaluating the Periplus of the Erythraean Sea - Boussac, M.F.; Salles, J.F.; Yon, J.B. (Brill | Manohar Publishers & Distributors, 2018)
Using the framework provided by the Periplus of the Erythraean Sea, a major maritime testimony dating from AD 40-70, this volume brings together philologists, historians and archaeologists to look closely at the interactions between the Mediterranean and the Indian Ocean world. Centered on the antiquity but with a long-term approach and designed as a contribution to the French commentary on the Periplus of the Erythraean Sea, this collection of papers relies on recent advances made in the field of ancient geography and text editing. It also takes advantage of ongoing fieldwork, both in terms of the archaeology of the establishments themselves, as well as the history of the techniques employed. They reveal the dynamics of commercial, religious and military networks, while granting full importance to the sui generis nature of the text: a continuum in the tradition handed down to us by classical antiquity and a major source on the relations between the Mediterranean and South-East Asia. Over half of the essays in the volume have been translated from French for the first time. The contributors include: Didier Marcotte, Pascal Arnaud, Johan Desanges, Bram Fauconnier & Patrice Pomey, Steven E. Sidebotham, Iwona Zych, Veronica Bucciantini & Michael D. Bukharin, Jeremie Schiettecatte, Axelle Rougeulle, Jean-François Salles, Federico de Romanis, Claude Allibert, Eric Vallet.